Regulación y función de la enzima Acil-CoA Sintetasa 4 involucrada en el control de los niveles de ácido araquidónico intracelular - Dattilo, Melina Andrea (2018)
Triple negative breast cancer (TNBC) tumors express higher ACSL4 levels compared to normal\ntissue. This enzyme promotes tumor aggressiveness by increasing cell migration, proliferation, and\ninvasion. In this work, ACSL4 human promoter was cloned and functionally characterized, demonstrating\nthat the transcription factor Estrogen Related Receptor Alpha (ERR?) is involved in the differential\nexpression of ACSL4 in breast cancer cell lines. ACSL4 and ERR? inhibition reduced cell proliferation by\na synergistic way. We also showed that estrogen receptor alpha exerts a negative regulation on ACSL4\nexpression, suggesting that both transcription factors participate in the regulation of the differential\nexpression of this enzyme in different models of breast cancer. Also, these results would explain ACSL4\noverexpression in TNBC tumors. We also analyze ACSL4 regulation and function in a neurosteroidogenic\nsystem. We demonstrated that in rat astrocytes, cAMP promotes ACSL4 induction and the stimulatory\naction of this enzyme in the increase of both StAR protein levels and steroid hormones. We also\ndemonstrated that ACSL4 exerts a modulatory effect on migration and proliferation of neurosteroidogenic\ncells.